Letter: Association of persistently high HBsAg levels during HBeAg‐seropositive stage and hepatocellular carcinoma risk in chronic hepatitis B patients—Authors' reply - Lin, Hsin‐Che; Jeng, Wen‐Juei; Yang, Hwai‐I (Alimentary pharmacology & therapeutics, 2024)
LINKED CONTENT This article is linked to Lin et al papers. To view these articles, visit https://doi.org/10.1111/apt.17915 and https://doi.org/10.1111/apt.17971